The incidence of side effects and their relation with anesthetic techniques after ambulatory surgery - (:unkn) unknown (Elsevier Ltd, 2003)
The aim of this study was to evaluate the incidence of side effects and their relation with anesthetic techniques in patient undergoing ambulatory surgery. 654 patients, ASA I-II, aged between 20 and 70 years scheduled for ambulatory surgery were enrolled into the study protocol. Patients were requested to record the existence of headache, sore throat, postoperative pain, nausea, vomiting, muscle weakness, lack of appetite, drowsiness, sleep disturbances, dizziness, dysuria, and lumbar pain during first week postoperatively. Postoperative pain was significantly higher after peripheral neural blockage. Muscle weakness, sore throat, lack of appetite, dysuria, sleep disturbances, headache, and dizziness were significantly higher after inhalational anesthesia (P<0.05). It was concluded that total intravenous anesthesia or neural blockade should be preferred for ambulatory surgery and an effective postoperative analgesic therapy should be planned before discharge. © 2003 Elsevier B.V. All rights reserved.
Keywords: Ambulatory surgery; Anesthetic techniques; Postoperative side effects